The problem of measuring the economic efficiency of advanced capital employment in the industry of Ukraine - Булаенко, Леонид Иванович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article stipulates that the total generated cost estimate of the manufacturing resources of the enterprise can be expressed in the form of advanced capital. There have been offered the overall indices of capital productivity ratio and profitability to measure the level and dynamics of economic efficiency of the advanced capital employment in the industry, their calculations and factorial analysis have been carried out. The proposals on the necessity to recommence the publication of the appropriate statistics to calculate the offered indices at the industrial level have been made.